Performance Analysis of Multi-Hop UAVs Using FSO Communications Under Humidity and Sandstorms Conditions - Mohammed Salih Mohammed Gismalla; Suhail I. Al-Dharrab; Saleh A. Alawsh; Ali H. Muqaibel (IEEE Open Journal of the Communications Society, 2024)
This paper investigates the performance of hovering unmanned aerial vehicles (UAVs) using free space optical (FSO) communications with decode-and-forward (DF) relaying. Multi-hop UAV relays are considered. The channel is modeled considering the atmospheric attenuation due to the sandstorm and relative humidity (RH), in addition to the atmospheric turbulence, angle-of-arrival (AOA) fluctuations, and pointing errors (PE). We first obtain a simplified expression for end-to-end (E2E) outage probability considering atmospheric attenuation conditions, then the impact of various parameters such as transmitted power, field of view (FOV) and optical beamwidth on E2E outage probability is incorporated. We also derive a closed form expression for the ergodic capacity and characterize the effect of different system parameters. Monte Carlo simulation is utilized to prove the analytical results. The asymptotic bound for E2E outage probability is validated to offer insights into the effects of different channel coefficients. Analysis of the results indicates that the impact of low visibility due to sandstorms is comparable to that of high RH on FSO links.